What should schools do to promote wonder?. (4th July 2021) - Wolbert, Lynne; Schinkel, Anders
ABSTRACT: Wonder-full education recognises experiences of wonder as lying at the heart of learning and education. If we accept the premise that wonder is important for/in education, what should characterise wonder-full education? This paper clarifies what it is like to wonder, how the aims of wonder-full education are best described, and it discusses three dimensions of wonder-full education: the educators, the curriculum, and the ethos of the classroom and school. It is argued that the success of a wonder-full curriculum hinges on the capacities of the teacher, both her pedagogical tact and her ability to wonder herself.